Factors affecting the nutritional status of school-aged children belonging to farming households in the Philippines - dela Luna, Kim Leonard G.; Talavera, Maria Theresa M.
"Undernutrition among school-aged children continues to be a public health concern in the Philippines, where agriculture is the primary source of income. School-age is a crucial phase of development and growth among children since it can establish nutritional knowledge and healthy eating habits across the next life stages. Evidence suggested that undernutrition exists among school-aged children belonging to households relying on agriculture" - title page.
Includes bibliographical references.
Keywords: Children -- Nutrition -- Philippines; Nutrition -- Philippines -- Evaluation; School-age child care -- Philippines